On the design and development of a handheld electrocardiogram device in a clinical setting - Alejandra Zepeda-Echavarria; Niek C. M. Ratering Arntz; Albert H. Westra; Leonard J. van Schelven; Froukje E. Euwe; Herke Jan Noordmans; Melle Vessies; Rutger R. van de Leur; Rutger J. Hassink; Thierry X. Wildbergh; Rien van der Zee; Pieter A. Doevendans; et al. (Frontiers Media S.A., 2024)
Cardiovascular diseases (CVDs) are a global burden that requires attention. For the detection and diagnosis of CVDs, the 12-lead ECG is a key tool. With technological advancements, ECG devices are becoming smaller and available for home use. Most of these devices contain a limited number of leads and are aimed to detect atrial fibrillation (AF). To investigate whether a four-electrode arrangement could provide enough information to diagnose other CVDs, further research is necessary. At the University Medical Center Utrecht in a multidisciplinary team, we developed the miniECG, a four-electrode ECG handheld system for scientific research in clinical environments (TRL6). This paper describes the process followed during the development of the miniECG. From assembling a multidisciplinary team, which includes engineers, cardiologists, and clinical physicians to the contribution of team members in the design input, design, and testing for safety and functionality of the device. Finally, we detail how the development process was composed by iterative design steps based on user input and intended use evolution. The miniECG is a device compliant for scientific research with patients within Dutch Medical Centers. We believe that hospital-based development led to a streamlined process, which could be applied for the design and development of other technologies used for scientific research in clinical environments.